EFEKTIVITAS KEARSIPAN DALAM MENINGKATKAN MUTU PELAYANAN ADMINISTRASI DI KELURAHAN TALANG SEMUT KECAMATAN BUKIT KECIL KOTA PALEMBANG - Abdullah, Zet (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This research aims to find out 1) archives management in sub-districts lompo riaja 2) Civil Service at the Talang Semut Subdistrict Office. In Data collection was carried out using observation, interviews and direct documentation. Data analysis techniques include collection stages data, data reduction, data presentation, data examination and drawing conclusions. This research resulted in 1) Records management in the office Talang Semut Subdistrict is not yet fully effective due to the level of effectiveness The archiving implementation implemented by Talang Semut Village is still in place in the unfavorable category. This is known from the way it is arranged and saving is still done manually. 2) As per the effort carried out by Talang Semut Subdistrict Office Employees in providing Good archival service means bringing in employees with resources better human resources and employees who understand the problems archives and services.